The private, the public, and the published: reconciling private lives and public rhetoric - Couture, Barbara, editor; Kent, Thomas, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2004)
At the 2003 "Rock the Vote" debate, one of the questions posed by a student to the eight Democratic candidates for the presidential nomination was "have you ever used marijuana?" Amazingly, all but one of the candidates voluntarily answered the question. Add to this example the multiple ways in which we now see public intrusion into private lives (security cameras, electronic access to personal data, scanning and "wanding" at the airport) or private self-exposure in public forums (cell phones, web cams, confessional talk shows, voyeuristic "reality" TV). That matters so private could be treated as legitimate-in some cases even vital-for public discourse indicates how intertwined the realms of private and public have become in our era. Reverse examples exist as well. Around the world, public authorities look the other way while individual rights are abused--calling it a private matter--or officials appeal to sectarian morés to justify discrimination in public policies. The authors of The Private, the Public, and the Published feel that scholarship needs to explore and understand this phenomenon, and needs to address it in the college classroom. There are consequences of conflating public and private, they argue--consequences that have implications especially for what is known as the public good. The changing distinctions between "private" and "public," and the various practices of private and public expression, are explored in these essays with an eye toward what they teach us about those consequences and implications.
Reconciling private lives and public rhetoric: what's at stake? -- Ain't nobody's business? A public personal history of privacy after Baird v. Eisenstadt -- Virtuosos and ensembles: rhetorical lessons from jazz -- Keeping the world safe for class struggle: revolutionary memory in a post-Marxist time -- Mary Putnam Jacobi and the speaking picture -- The collective privacy of academic language -- The essayist in and behind the essay: vested writers, invested readers -- Upon the public stage: how professionalization shapes accounts of composing in the academy -- Ethical deliberation and trust in diverse-group collaboration -- Identity and the Internet: the telling case of Amazon.com's top fifty reviewers -- The influence of expanded access to mass communication on public expression: the rise of representatives of the personal -- Private witness and popular imagination -- Mixing it up: the personal in public discourse -- Cultural autobiographics: complicating the "personal turns" in rhetoric and composition studies -- Going public: locating public/private discourse -- Public writing and rhetoric: a new place for composition.
Keywords: Rhetoric; Written communication; Privacy, Right of